Legal Protection for People with Disabilities in the Perspective of Human Rights in Indonesia - Abduladjid, Syawal (2021)
The purpose of this research is to find out how the principles of legal protection for persons with disabilities and how the implementation of legal protection for persons with disabilities. Indonesia has strong legal principles in making Indonesia a constitutional state with the existence of regulations on guarantees for the protection and empowerment of persons with disabilities which are reflected in; Pancasila as the state philosophy, the Preamble of the 1945 Constitution, Law, TAP MPR, Conventions and International Declarations on human rights. Likewise, legal recognition of persons with disabilities can be seen from the regulations, both Indonesian state regulations, and regulations, or international organizations that provide legal guarantees for the rights of persons with disabilities